Prévalence de la coronaropathie chez les survivants d’accident vasculaire cérébral à Parakou (Bénin) en 2019 - Houehanou, Yessito Corine Nadège (Pan Afr Med J, 2021)
INTRODUCTION: coronary artery disease seem common in stroke patients. We aimed to determine the prevalence of coronary artery disease in stroke survivors followed at the Borgou-Alibori Departmental University Hospital (CHUD/B-A). METHODS: this was a cross-sectional study, conducted from March 1 to August 31, 2019. It included all stroke patients, aged ≥ 18 years, received in the neurology unit of CHUD-B/A between January 2012 and July 2019, having survived the acute phase, and from whom written informed consent or that of a guardian (severely disabled patients) has been obtained. An individual interview, anthropometric measurements, a physical examination, an electrocardiogram record and a review of the medical record were performed. The coronary artery disease was defined by a documented history, suggestive ST/T and/or Q abnormalities (Minnesota criteria) or a positive angina screening questionnaire. The factors associated with coronary artery disease were investigated by logistic regression. RESULTS: a total of 101 patients were included with an average age of 57.2 ± 10.5 years. The median time since stroke onset was 11 months (interquartile range: [2.0-23.5]). Ischemic stroke predominated (57.4%). The prevalence of coronary artery disease was estimated at 49.5%. The factors associated were lack of school education (p=0.036), obesity (0.036) and former tobacco use (p=0.044). CONCLUSION: this study shows a high frequency of coronary artery disease in stroke patients. It is important to detect coronary artery disease in this target population in order to improve the management.